Female sterilization paradoxical association with premature menopause in Bihar - Karan Babbar (Scientific Reports, 2025)
Abstract Premature menopause is a growing public health crisis with serious implications for women’s well-being. While premature menopause prevalence varies across India, Bihar’s rates are exceptionally high (11%), warranting specific investigation. Analyzing data from National Family Health Survey-5, this study examines state-level variations and predictors of premature menopause, focusing on the context of Bihar. Bihar’s premature menopause rates were significantly higher than in other states, even after controlling for hysterectomy, suggesting unique regional drivers. While lower education, more children, and younger age at first and last birth were risk factors across India, this is especially concerning in Bihar. I found a strong association between female sterilization and both naturally occurring and hysterectomy induced premature menopause in Bihar, despite its intended role in family planning. This paradoxical finding, coupled with the protective effect of contraceptive use, raises critical questions about the potential unintended consequences of sterilization practices in Bihar and highlights the need for comprehensive reproductive healthcare services. The study underscores the urgent need for targeted public health interventions, including investments in girls’ education, expanded reproductive healthcare options beyond sterilization, improved sterilization practices through stricter regulation and provider training, and further investigation into the complex factors driving Bihar’s high premature menopause rates.